Building Digital Stories: Architecture and Cartography Meet Documentary and Journalism. (5th September 2018) - Killing, Alison
Abstract : Architects' skills of spatial analysis and representation can be put to good use in surprisingly diverse fields. In the case ofAlison Killing, whose studio Killing Architects is based in Rotterdam, they serve to raise public awareness and understanding of topical issues such as migration and climate change. She reveals what motivated her to branch out in this direction, describes a recent self‐initiated project in detail, and notes how the Netherlands' well‐known culture of encouraging designers to pursue research has helped.